Examining the Intersection of Bullying and Physical Relationship Violence Among New York City High School Students. Issue 1 (January 2017) - Peters, Zachary J.; Hatzenbuehler, Mark L.; Davidson, Leslie L.
Research is just beginning to explore the intersection of bullying and relationship violence. The relationship between these forms of youth aggression has yet to be examined in diverse urban centers, including New York City (NYC). This study seeks to identify intersections of joint victimization from bullying and electronic bullying (e-bullying) with physical relationship violence (pRV). This study examines data from the NYC Youth Risk Behavior Survey (YRBS), a representative sample of NYC public high school students, to assess the concurrent victimization from bullying at school and e-bullying with pRV, operationalized as physical violence by a dating partner in the past 12 months. Students who reported being bullied at school and e-bullied had increased odds (bullied: OR = 2.5, 95% CI [2.1, 2.9]; e-bullied: OR = 3.0, 95% CI [2.6, 3.5]) of also being victimized by pRV compared with those who did not report being bullied or e-bullied. In logistic regression models, being bullied at school and being e-bullied remained significant predictors of students' odds of reporting pRV (bullied: AOR = 2.6, 95% CI [2.2, 3.1]; e-bullied: AOR = 3.0, 95% CI [2.5, 3.6]) while controlling for race, gender, sexual orientation, and age. This research is the first to assess the intersection of victimization from bullying and e-bullying with pRV in a large, diverse, random sample of urban high school students. In this sample, students who report being bullied or e-bullied are more likely also to report pRV than students who have not been bullied or e-bullied. This research has potential implications for educators, adolescent health and social service providers, and policy makers to tailor programs and enact policies that jointly address bullying and pRV. Future studies are needed to longitudinally assess both victimization from and perpetration of bullying and pRV.